Pete the cat : I love my white shoes - Litwin, Eric.; Dean, James, 1957- (New York : Harper, 2010)
Pete the Cat wears his new white shoes while walking down the street, and as he steps into piles of strawberries, blueberries, and other messes--and the color of his footwear changes--he keeps on moving and singing to himself without being bothered.
Horn Book
Horn Book, October 2010
1.3
Preschool.
Preschool
Keywords: Cats -- Juvenile fiction; Shoes -- Juvenile fiction; Singing -- Juvenile fiction; Cats -- Fiction; Shoes -- Fiction; Singing -- Fiction; Stories in rhyme; Cats -- Fiction; Shoes -- Fiction; Singing -- Fiction; Stories in rhyme; Picture books for children